2021
DOI: 10.3399/bjgp.2021.0194
|View full text |Cite
|
Sign up to set email alerts
|

Out-of-hours services and end-of-life hospital admissions: a complex intervention systematic review and narrative synthesis

Abstract: Background: Out-of-hours hospital admissions for end-of-life care patients are a common cause for concern to patients, families, clinicians and policy makers. It is unclear what issues, or combinations of issues, lead out-of-hours clinicians to initiate hospital care for these patients. Aim: To investigate the circumstances, processes and mechanisms of UK out-of-hours services-initiated end-of-life care hospital admissions. Design and Setting: Systematic literature review and narrative synthesis. Method: Eight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…A long-standing GP-patient relationship is known to reduce the use of OOH-service and hospital admissions in the general population [ 46 ]. Furthermore, it is known that continuity of care in primary care is important when organizing palliative care [ 45 , 47 ], and according to a systematic review from 2021, the lack of continuity of care is associated with end-of-life hospital admissions OOH [ 48 ]. A recent Norwegian study found that GPs find it hard to avoid OOH hospital admissions if they have not been involved in the care of the patients [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…A long-standing GP-patient relationship is known to reduce the use of OOH-service and hospital admissions in the general population [ 46 ]. Furthermore, it is known that continuity of care in primary care is important when organizing palliative care [ 45 , 47 ], and according to a systematic review from 2021, the lack of continuity of care is associated with end-of-life hospital admissions OOH [ 48 ]. A recent Norwegian study found that GPs find it hard to avoid OOH hospital admissions if they have not been involved in the care of the patients [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Eight emergency issues were flagged as prevalent, and several minor medical issues were consistently raised. Given the need to triage for hospital admission (or render initial management) mentioned before and big role of phone-based support (at least till the next workday), customised staff training including resource aides could be produced [7,12,17]. Second, like others before [5,12], work improvement efforts around better 'in-hours' communication to reduce the need to 'clarify care plans' (17.6% of calls) and deliberate advice on procedures after death to minimise calls 'informing that patient has died' (10.5% of calls) are worth looking into [7,15,19].…”
Section: Discussionmentioning
confidence: 99%
“…After-hours palliative care support is a lifeline to patients with serious medical conditions who choose to spend more days at home rather than an institution like hospital or hospice [1][2][3][4][5][6][7][8]. Operating a 24/7 telephone helpline is fundamentally how most services render out of hours support.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 There are recurrent problems in the provision of out-of-hours care, including the challenge of co-ordinating care between different services, uncertainties around prognostication and decision-making about admission to hospital, while taking into account the capacity to care (by informal and formal carers) for the patient at home and the wishes of patient and family. 14 , 15 To date there is a lack of agreement about which models of care (and which components of these models), including out-of-hours provision, provide good quality care for patients and families near end of life. 16 …”
Section: Introductionmentioning
confidence: 99%